Traditional roles of women in farm operations in Sagamu Local Government Area, Ogun State, Nigeria (2004)
This study investigated women's roles in soil management in Sagamu Local Government Area, Ogun State, Nigeria, Using a random sampling technique, 90 women farmers were selected from 619 registered women farmers in Sagamu Local Government Area, The results indicate that majority (68,9%) of the women were married, and in their active ages (25- 45 years). Majority (97.6%) adopted multiple cropping system, while weeding as well as pest and disease control were manually done (92.8%). Also, 53.3% of them used resistant crop varieties. The use of cover crop for maintenance of soil-fertility was widespread (61.1 %). Between 49.9% and 94.4% of the women had control over their farming operations while 45.6% - 46.7% indicated that their spouses took decisions on land and related issues. Water logging was a major problem (57%) on women's farmlands. It is suggested that regular soil management programmes be organized for women in Sagamu LGA by extension and related organizations to enable the women solve soil problems on their farms and increase productivity. The establishment of soil management centres in the study area will help disseminate relevant information on soil management practices to the women.